MEMBANGUN MODERASI BERAGAMA MELALUI BARIKAN PUNDEN DI DESA TERNADI - Mu'ayyadah Mu'ayyadah; Noor Fatmawati; Dany Miftah M Nur (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2022)
The purpose of this study was to describe the punden in Ternadi Village, namely Sunan Kaliyetno, Petilasan Mbah Njokowono, Nyai Soemarsih, Nyai Satirah, and Kyai Jenggot in Ternadi Village. Second, is to describe the values ​​of moderation which consist of four things, namely the value of local wisdom, the value of tolerance, the value of national insight, and the value of anti-violence. The third is to describe the application of religious moderation through the punden punden Sunan Kaliyetno, Petilasan Mbah Njokowono, Nyai Soemarsih, Nyai Satirah, and Kyai Jenggot. The data collection technique used descriptive qualitative methods which included interviews, observations, and documentation. The data analysis uses the method from Miles Huberman, namely collecting data, selecting data, presenting data, and drawing conclusions/interpretations. The results of the research obtained are the practice of religious moderation carried out by the Ternadi community through local wisdom in the form of punden Sunan Kaliyetno, Petilasan Mbah Njokowono, Nyai Soemarsih, Nyai Satirah, and Kyai Jenggot. The conclusion is that the punden at Ternadi can be an application of religious moderation so as to strengthen brotherhood among the community.